2012
DOI: 10.1111/j.1365-2095.2011.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous light induces bone resorption and affects vertebral morphology in Atlantic salmon (Salmo salarL.) fed a phosphorous deficient diet

Abstract: This study investigated the combined effects of photoperiod and dietary P level on bone osteoclast and osteoblast activity, and morphology, as well as plasma vitamin D status in Atlantic salmon post‐smolts. The fish were reared under continuous light (LL) or 12 h light/dark (LD) per day, and fed diets with insufficient phosphorous (P) (4 g kg−1 available dietary P, LP) or sufficient P (8 g kg−1 available dietary P, HP) for 79 days in seawater. LL significantly increased plasma 25(OH)D3 level and bone tartrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…Alp and mmp13 are responsible for bone formation and mineralisation and cartilage and bone resorption, respectively [7379]. In Atlantic salmon, all these genes have been already shown to be differential expressed in poorly mineralised and deformed vertebrae relative to normal vertebrae [8, 80, 81]. The current study suggests their involvement in the development of a skeletal anomaly affecting the lower jaw in Atlantic salmon.…”
Section: Discussionmentioning
confidence: 60%
“…Alp and mmp13 are responsible for bone formation and mineralisation and cartilage and bone resorption, respectively [7379]. In Atlantic salmon, all these genes have been already shown to be differential expressed in poorly mineralised and deformed vertebrae relative to normal vertebrae [8, 80, 81]. The current study suggests their involvement in the development of a skeletal anomaly affecting the lower jaw in Atlantic salmon.…”
Section: Discussionmentioning
confidence: 60%
“…(2010a) found that a group of postsmolts with a high mRNA expression level in vertebral bone of MMP‐13 (Matrix MetalloProteinase 13), which codes for a protein belonging to a family of proteins involved in the degradation of the extracellular matrix, developed a high percentage of fish with compressions later on. Furthermore, the development of vertebral deformities has been associated with an increase in TRACP enzyme activity in vertebral bone in Atlantic salmon (Fjelldal et al., 2012a), which shows that matrix degradation may play an important role in the pathogenesis of vertebral deformities in Atlantic salmon. Ytteborg et al.…”
Section: Causes and Pathogenesis Of Vertebral Deformitiesmentioning
confidence: 99%
“…Vitamin A, for example, has an antagonistic effect on vitamin D by reducing the concentration of calcitriol (Ørnsrud et al., 2009). Furthermore, the vitamin D system is affected by the photoperiod (Fjelldal et al., 2012a). Removal of the light sensitive pineal gland (Fjelldal et al., 2004), photoperiod manipulation (Fjelldal et al., 2005; Wargelius et al., 2009), and water temperature (growth rate) elevation (Grini et al., 2011) all affects vertebral bone mineralization in Atlantic salmon.…”
Section: When and Why Do Vertebral Deformities Develop?mentioning
confidence: 99%
“…Thus, the transcription of this gene may as well be linked to the impaired ossification front in the arches, as described previously in this paper. It has already been shown that diets with low or suboptimal levels of P may change gene and protein activity in salmon reared under continuous light, like changed concentration of the active vitamin D hormone 1,25 OH 2 D 3 , a subsequent increase in ALP activity and reduction in TRACP activity in bone (Fjelldal et al, 2012a). In this study, no stimulation in bone ALP activity or plasma 1,25 OH 2 D 3 was observed in the low P group, despite severe morphological changes in the bone, consistent with inadequate dietary P. Salmon fry given diets containing 0.5, 0.7 and 1.4% soluble P from first feeding to 50 g showed a clear dose-response for these enzymes, with the highest ALP and low TRACP activity at low P intake (Fjelldal et al, 2012b).…”
Section: Figmentioning
confidence: 98%